Advertising as discursive reflections of the political realm: Turkish-Cypriot advertisements between 1940-1974. (9th February 2023) - Yalkin, Cagri; Kahveci, Hayriye; Uygur, Kubra
Abstract : Purpose: The purpose of this paper is to explore how conflict/war and its political economic and socio-cultural reflections influenced Turkish-Cypriot advertisements. It provides an analysis of the Turkish-Cypriot advertisements during 1940–1974, which was characterised by intermittent inter-ethnic armed conflict, to illuminate how they are related to the commercial, political, economic and socio-cultural unravelling of the era. Design/methodology/approach: Compositional interpretation and social semiotic analysis (Rose, 2016) with a critical lens have been adopted as research design. Social, cultural, economic and political conditions of the time were also used in the analysis. Findings: Firstly, this paper shows that the advertisements increased in complexity although very incrementally through the studied period, especially in comparison to the advertising of the countries that directly influenced the commercial sphere in Cyprus such as Britain, Greece and Turkey. Secondly, this paper shows that the advertisement messages were directly shaped by key events in the socio-political realm. Especially during the 1940s (British rule) and the bicommunal Republic of Cyprus era, the Turkish-Cypriot community newspapers featured a cosmopolitan range of advertisements paid for by Greek-Cypriot, Armenian-Cypriot and Turkish-Cypriot businesses. After 1963, when the armed conflict began and the communities retreated to separate parts of the capital city, the featured advertisements mostly reverted back to the 1950s political economic agenda: firstly, they intended to build ethno-community consciousness by transforming Turkish-Cypriots who were scattered around in different towns, villages and cities into a public/community; secondly, they were used in developing the burgeoning Turkish-Cypriot business enterprises and the making of a consumer class. Originality/value: As no such study was conducted so far, this paper shows, through the continued and increasing existence and variety of the advertisements printed in Turkish-Cypriot newspapers, the trajectory with which the Turkish-Cypriots met the consumption codes of the era under armed conflict. Secondly, the authors observe the "state" authority (in this case, the community administration) directly and indirectly influences both the business agenda and the building of community consciousness. Thirdly, the authors show that the Turkish-Cypriot community had normalised commerce under armed-conflict.